COMPARATIVE CHARACTERISTIC OF THE RESULTS OF CLINICAL STUDIES OF THE MUCOUS FLAPS IN THE EARLY STAGES OF OBSERVATION DURING THE BONE AUGMENTATION OF THE MANDIBLE USING TITANIUM MESH - Kaplun, D.V.; Avetikov, D.S.; Vakulenko, K.M.; Boyko, I.V.; Gavrilyev, V.M. (World of Medicine and Biology, 2019)
One of the main problems in restoring the lost bone mass in pretreatment patients for dental implantation is the exposure of bone augmentate and its infection as a result of ischemic processes in the mucous graft that covers it. Such phenomena occur as a result of overstretching of the mucous graft. To date, the level of complications during bone augmentation remains stably high. We performed 27 surgical treatment bone augmentation using a titanium mesh according to the classical method of the detachment of a trapezoidal mucous graft and 30 surgical treatment according to the author’s method of detachment and mobilization of the mucous graft. Our studies have shown that the optimization of the boundaries of detachment and mobilization of mucous and mucoperiosteal grafts compared to the classical trapezoidal graft technique leads to a decrease in hyperemia, a reduction in the duration of edema, a decrease in pain, and most importantly, a decrease in cases of necrotization of the mucous graft. Clinical observations are also confirmed by a decrease in the temperature of the operated wound. The data indicate the possibility of increasing the efficiency of graft operations during bone augmentation for patients with secondary adentia and reducing the risk of postoperative complications caused by ischemia of the mucous grafts as a result of their tension. The results obtained are useful for practicing dental surgeons when planning bone augmentation surgery on the lower jaw.
Keywords: bone augmentation; flap surgery; mucous membrane